Morphological and seismostratigraphic evidence of Quaternary mass transport deposits in the North Ionian Sea: the Taranto landslide complex (TLC) - Meo, Agostino; Senatore, Maria Rosaria (Frontiers in Earth Science, 2023)
This paper regards the Taranto Landslide Complex (TLC), a large submarine landslide area located along the continental margin of the Puglia Region, in the Gulf of Taranto (North Ionian Sea), between 200 and 800 m water depth. Based on very high resolution multibeam data, a morphological analysis is performed by measuring different physical and spatial parameters (i.e. surface, headwall height and length, slope in the source area, blocks in the accumulation zone). In addition, we use nine high resolution sub-bottom CHIRP profiles to reconstruct the stratigraphic architecture. The main results show the occurrence of five phases of Quaternary Mass Transport Deposits (MTDs) in the study area. From the oldest to the youngest Mass Transport Deposits we have: MTD1, with a volume of about 0.032 km3 and an area of about 4 km2; MTD2, which is the largest of the identified deposits, covers an area of ~26 km2 and has an estimated volume of ~0.35 km3; MTD3 and MTD4 with volumes of about 0.033 km3 and 0.035 km3 and an area of 7 km2 and 5 km2 respectively. The last one submarine landslide is represented by MTD5 which has a volume of 0.02 km3. The deposits are internally characterized by chaotic acoustic facies with reflectors with moderate amplitude and laterally continuous at time showing a likely erosive characters defined as “Bounding Surfaces” (BS). The main transport direction of the MTDs is supposed to be from north/northeast to south/southwest. It represents the trend of the continental slope, but there are also slope failure evidence coming from west/northwest to east/southeast (MTD5).